Novel Applications of FIB-SEM-Based ToF-SIMS in Atom Probe Tomography Workflows - Rickard, William; Reddy, Steven; Saxey, David; Fougerouse, Denis; Timms, Nick; Daly, L.; Peterman, E.; Cavosie, Aaron; Jourdan, Fred (2020)
Copyright © Microscopy Society of America 2020. Atom probe tomography (APT) is used to quantify atomic-scale elemental and isotopic compositional variations within a very small volume of material (typically <0.01 μm3). The small analytical volume ideally contains specific compositional or microstructural targets that can be placed within the context of the previously characterized surface in order to facilitate a correct interpretation of APT data. In this regard, careful targeting and preparation are paramount to ensure that the desired target, which is often smaller than 100 nm, is optimally located within the APT specimen. Needle-shaped specimens required for atom probe analysis are commonly prepared using a focused ion beam scanning electron microscope (FIB-SEM). Here, we utilize FIB-SEM-based time-of-flight secondary ion mass spectrometry (ToF-SIMS) to illustrate a novel approach to targeting <100 nm compositional and isotopic variations that can be used for targeting regions of interest for subsequent lift-out and APT analysis. We present a new method for high-spatial resolution targeting of small features that involves using FIB-SEM-based electron deposition of platinum "buttons" prior to standard lift-out and sharpening procedures for atom probe specimen manufacture. In combination, FIB-ToF-SIMS analysis and application of the "button" method ensure that even the smallest APT targets can be successfully captured in extracted needles.